Potret Kehidupan Ibu Rumah Tangga dalam Peningkatan Ekonomi Keluarga Nelayan - Musa, Farid Th.; Hatu, Dewinta Rizky R.; Karu, Novia Fharitsha (Program Studi Sosiologi, Fakultas Ilmu Sosial Universitas Negeri Gorontalo, 2024)
The village of Oluhuta is one of the villages located within the territorial jurisdiction of Kabila Bone Subdistrict. In Oluhuta Village, Kabila Bone Subdistrict, several housewives actively contribute to improving family economies, with some of them being women engaged in fishing. This research aims to uncover the roles, challenges, and strategies faced by housewives in supporting the economic growth of fishermen's families. The research employs a qualitative descriptive method, collecting data through observation, interviews, and documentation. The gathered data will be reduced, presented with brief descriptions, and conclusions will be drawn. The findings indicate that there are factors leading housewives to become fishermen, such as inadequate income from husbands and the rising cost of living, prompting them to seek employment. Additionally, some housewives have a passion for fishing from childhood, not solely driven by economic necessity but as a lifelong habit.